Digital governance : leading and thriving in a world of fast-changing technologies - Swinfen Green, Jeremy; Daniels, Stephen (Routledge, 2020)
"Digital Governance provides managers with a simple and jargon-free introduction to the impact that digital technology can have on the governance of their organisations. Digital technology is at the heart of any enterprise today, changing business processes and the way we work. But this technology is often used inefficiently, riskily or inappropriately. Worse perhaps, many organisational leaders fail to grasp the opportunities it offers and thus fail to "transform" their organisations through the use of technology. This book provides an explanation of the basic issues around the opportunities and risks associated with digital technology. It describes the role that digital technology can play across organisations (and not just behind the locked doors of the IT department) giving boards and top management the insight to develop strategies for investing in and exploiting digital technology as well as arming them with the knowledge required to ask the right questions of specialists and to detect when the answers given are evasive or irrelevant. International in its scope, this essential book covers the fundamental principles of digital governance such as leadership, capability, accountability for value creation and transparency of reporting, integrity and ethical behaviour"--